2004
DOI: 10.1038/sj.npp.1300415
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Nicotine Maintenance Attenuates the Subjective and Reinforcing Effects of Intravenous Nicotine, but not Cocaine or Caffeine, in Cigarette-Smoking Stimulant Abusers

Abstract: The effects of transdermal nicotine maintenance on the subjective, reinforcing, and cardiovascular effects of intravenously administered cocaine, caffeine, and nicotine were examined using double-blind procedures in nine volunteers with histories of using tobacco, caffeine, and cocaine. Each participant was exposed to two chronic drug maintenance phases (21 mg/day nicotine transdermal patch and placebo transdermal patch). Within each drug phase, the participant received intravenous injections of placebo, cocai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…This ensured that participants who were smokers had completed all discounting tasks within ~2 hours of smoking to minimize the potential effects of nicotine withdrawal on study outcome measures. Moreover, previous human research suggests no interaction between nicotine maintenance vs. abstinence on cocaine subjective effects (Sobel et al, 2004). …”
Section: Methodsmentioning
confidence: 92%
“…This ensured that participants who were smokers had completed all discounting tasks within ~2 hours of smoking to minimize the potential effects of nicotine withdrawal on study outcome measures. Moreover, previous human research suggests no interaction between nicotine maintenance vs. abstinence on cocaine subjective effects (Sobel et al, 2004). …”
Section: Methodsmentioning
confidence: 92%
“…In human laboratory studies, cocaine administration demonstrated increased rates of cigarette smoking (58, 59), and acute nicotine dosing by transdermal nicotine patch (22 mg) increased cue-induced cocaine craving in individuals with a history of cocaine use (60). Mixed findings also demonstrate a decrease or no change in subjective effects of cocaine following pretreatment with nicotine patch in occasional and heavy cocaine users, respectively (61, 62). More recently, a human laboratory study demonstrated that cocaine users exhibit an orienting, but not attentional, bias towards cigarette cues versus non-cocaine users, and that cocaine users demonstrate increased urge to smoke cigarettes for negative reinforcement versus non-users (63).…”
Section: Nicotine and Other Drugs Of Abusementioning
confidence: 93%
“…The MCP has been validated with tobacco products and nicotine [17, 18, 19, 20, 21], corresponds with other measures of reinforcement [16, 17], is sensitive to manipulation of study parameters (e.g., smoking deprivation, smoking cues) [17, 18], and can be used to determine the reinforcing efficacy of cigarettes/nicotine relative to other drugs, doses, or combinations (e.g. relative abuse liability) [19, 20, 21]. With the MCP, participants sample the novel drug and then make two or more discrete choices between it and 1) another drug/preparation or 2) a series of monetary values [16].…”
Section: Introductionmentioning
confidence: 99%